Hemodynamic homeostasis disequilibrium in critical illness - Wang, Jie; Wang, Xiaoting; Liu, Dawei; Lian, Hui; Wang, Guangjian; Tong, Zewen; Deng, Qingyu; Guo, Qirui; Zhang, Qian; Chao, Yangong; Yin, Wanhong (Frontiers in Physiology, 2025)
Over millions of years, the circulatory system evolved from primitive forms into a highly specialized network capable of overcoming time-distance constraints and enhancing diffusion efficiency. This structural advancement laid the physiological foundation for the regulation of hemodynamics and systemic homeostasis. Hemodynamic homeostasis is a fundamental biological process that ensures the continuous delivery of oxygen and substrates while facilitating the removal of carbon dioxide and metabolic waste. Such balance is essential for sustaining cellular metabolism and maintaining the function of vital organs throughout embryonic development and the human lifespan. Disruption of this equilibrium, primarily driven by the Host/Organ Unregulated Response (HOUR), compromises the cardiovascular-respiratory system, resulting in hemodynamic homeostasis disequilibrium. HOUR specifically targets the critical unit—a constellation of elements essential for oxygenation and cell energetics, including the microcirculation, endothelial glycocalyx, and mitochondria, impairing the oxygenation process, ultimately triggering critical illness. Although intervention targeting systemic hemodynamic variables (e.g., pressure, flow) may temporarily improve regional perfusion, restoring full homeostasis remains challenging. This is largely due to the activation of multiple positive feedback loops (e.g., coagulation cascades) and impairment of key negative feedback mechanisms (e.g., blood pressure regulation). In the presence of ongoing HOUR, inappropriate or delayed interventions may exacerbate injury and accelerate irreversible organ damage or death. Therefore, it is both essential and urgent to elucidate the initiation, recognition, progression, and modulation of hemodynamic homeostasis disequilibrium.